Knitted animal scarves, mitts and socks : 35 fun and fluffy creatures to knit and wear - Goble, Fiona (Cico Books, 2015)
A book with simple stitches, full instructions for making-up and clear photographs presents more than 30 animal-themed knitting projects, including a Tropical Frog Scarf, Penguin Socks and a Bear Scoodie. Original.